2016
DOI: 10.3389/fmicb.2016.01010
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of the C-Terminal Domain of the Salmonella enterica PduO Protein: An Old Fold with a New Heme-Binding Mode

Abstract: The two-domain protein PduO, involved in 1,2-propanediol utilization in the pathogenic Gram-negative bacterium Salmonella enterica is an ATP:Cob(I)alamin adenosyltransferase, but this is a function of the N-terminal domain alone. The role of its C-terminal domain (PduOC) is, however, unknown. In this study, comparative growth assays with a set of Salmonella mutant strains showed that this domain is necessary for effective in vivo catabolism of 1,2-propanediol. It was also shown that isolated, recombinantly-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The second example is the C-terminal domain of a protein PduO (PduOC) playing an important role in the catabolism of 1,2-propanediol in the pathogenic bacterium Salmonella enterica (PDB-ID: 5cx7, chain E) [24]. Fig 8C presents the structure of PduOC co-crystallized with heme, whose binding mode significantly differs from those in other members of this protein family.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second example is the C-terminal domain of a protein PduO (PduOC) playing an important role in the catabolism of 1,2-propanediol in the pathogenic bacterium Salmonella enterica (PDB-ID: 5cx7, chain E) [24]. Fig 8C presents the structure of PduOC co-crystallized with heme, whose binding mode significantly differs from those in other members of this protein family.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, heme was identified as a physiological ligand of orphan nuclear receptors REV-ERBα and REV-ERBβ, extending the collection of known ligands of the human nuclear receptor family beyond endocrine hormones and dietary lipids [23]. Despite the fact that the PDB contains about 3,600 proteins complexed with some form of heme, new binding modes of heme are still being discovered [24]. Therefore, a reliable classification and characterization of binding sites in hypothetical proteins may support studies focused on the identification of physiological ligands and their binding modes.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins with DUF336 domains are present in single- or multi-domain proteins and their genetic association with gene clusters that encode well-characterized pathways such as glycolate utilization in E. coli (GlcG), 1,2-propanediol utilization in Salmonella enterica (PduO), and chloroaniline degradation in Diaphorobacter sp. PCA039 (OrfU2) has been noted [8286]. The two best characterized examples are HbpS of S. reticuli and PduO of S. enterica .…”
Section: Discussionmentioning
confidence: 99%
“…HbpS is located extracellularly where it senses and degrades heme and activates a two-component system involved in oxidative stress [88,92,117,118]. PduO is localized to the pdu microcompartment its DUF336 domain is fused to an ATP:cob(I)alamin adenosyltransferase domain; its DUF336 domain is not required for the activity of the ATP:Cob(I)alamin adenosyltransferase domain in vitro but is required for optimal 1,2-propanediol utilization for unknown reasons [86]. Both HbpS and PduO have been shown to bind heme and cobalamin but their cellular locations are distinct, consistent with their disparate functions.…”
Section: Discussionmentioning
confidence: 99%
“…AdoCbl is the coenzyme of the 1,2-propanediol dehydratase that converts 1,2-propanediol to propionaldehyde 13 . In-depth studies of CobA and PduO have been reported, and structures with substrates bound to them have been elucidated 6, 1416 . EutT class of ACATs are not as well understood.…”
Section: Introductionmentioning
confidence: 99%